The Impact of the Principal’s Leadership on Teacher Performance in History at Palu State High School 5 - Wiranto G. Baharu; Iskandar Iskandar; Misnah Misnah; Mahfud,M. Gamar; Minarni Nongtji (FKIP - Universitas Riau, 2026)
Education is a pillar of national development because it determines the quality of human resources. The leadership of school principals plays a strategic role in enhancing the motivation and performance of teachers, particularly history teachers, who play a vital role in shaping students’ character and competencies. This study aims to analyze the contribution of school principal leadership to the performance of history teachers at Palu State High School 5 and to describe teachers’ performance achievements in the classroom. The study employs a qualitative approach using the case study method. The research subjects included the principal, the vice principal for curriculum, history teachers, and students in grades 11–12. Data were collected through interviews, observations, and documentation, then analyzed using qualitative descriptive methods involving data reduction, narrative presentation, and drawing conclusions. The results indicate that the principal effectively fulfills a dual role as a supervisor, evaluator, and motivator. The principal guides teachers through formal and informal supervision, routinely monitors and evaluates learning, and encourages professional development by creating a conducive environment and providing recognition. This leadership contributes positively to the performance of history teachers, as evidenced by their mastery of subject matter, effective use of class time, appropriate pedagogical strategies, use of instructional media, and educational interactions with students. As a result, the principal’s leadership has enhanced professionalism, discipline, creativity, and the quality of education at Palu State High School No. 5.